Study of Anemia, Hemoglobin Level, and Subjective Well-being among Women of Reproductive Age in Indonesia - Suwarni, Linda (Poltekkes Kemenkes Palu, 2023)
Anemia is a burden for women of reproductive age (15 – 49 years old) which in Indonesia takes 22.3% of prevalence based on Basic Health Survey data in 2018. Women of reproductive health have different points of view according to their subjective well-being. This study aimed to examine the correlation between anemia status and hemoglobin level related to subjective well-being among women of reproductive age. This cross-sectional study used the Indonesia Family Life Survey (IFLS) wave 5 in 2014/15 with a total study sample were 12,818. Subjective well-being is self-reported data with categories satisfied, somewhat satisfied, and not satisfied. Hemoglobin level is measured by blood test and if the Hb level is less than 12, it will be categorized as anemia. This study tested the analysis of univariate, bivariate (Chi-square and ANOVA), and multivariate (multinomial logistic regression) using STATA version 17. The findings revealed that anemia and hemoglobin levels did not have a correlation with subjective well-being. However, some other covariates were found significantly associated with having satisfied subjective well-being including being married, pregnant, having poor SES, more than adequate of family life satisfaction, and adequate and more than adequate standard of life, with RRR 1.21, 1.21,0.63, 1.77, 1.19, and 1.74, respectively. It is concluded that subjective well-being is associated with not only health aspects but also social and economic. Intervention in the level of community is needed to improve the quality of life to achieve satisfied well-being. For example by joining the social group at the village level. Future study can include other health-based predictors at individual level that potentially predict subjective well-being.